On The Process Of Thematic Consolidation Of Legal Terms - et. al., Muyassarkhon Bakhriddinova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is dedicated to the process of thematic consolidation of legal terms. It is evident that terms are commonly utilized in many realms including technology, science, art, literature and law. They have been studied for many years by plenty of scholars since they own primary and secondary meanings. The advancement of cutting-edge technologies has brought about many changes in terminology as well and various terms have appeared in every field. Indeed, law is a very broad area with its differently used words, phrases and word combinations. Nowadays, new terms have also been created in this sphere and they have to be learnt very thoroughly. Presently, lots of presidential decrees and rules have been enacted in a bid to develop law system; therefore, studying legal terms is a must for every linguist working in this field. As W.Shuy stated the main duty of linguists is to help untangle the language confusion (p. 12). Hence, we attempted to present some peculiarities of legal words and differences in their usage.